PENGARUH EFEKTIFITAS PELATIHAN DAN DISIPLIN KERJATERHADAP KINERJA PEGAWAI PADA KANTOR PENCARIAN DAN PERTOLONGAN KELAS B MAUMERE KABUPATEN SIKKA - Agustinus Logho Bata; Immanuel Wellem; Paulus Juru (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The background of this which was attributed to issues rela not aligning with existing regulations. This study aimed to (1) describe employee performance, training effectiveness, and work discipline, and (2) analyze the influence of training effectiveness and work discipline on employee performance both partially and simultaneously. The population in this study consisted of 40 employees at the Class B Search and Rescue Office, Sikka Regency. Using the Slovin formula, the sample size was determined to be 40 employees. Data were collected through questionnaires and analyzed using descriptive and inferential statistical methods, specifically multiple linear regression. Hypothesis testing was conducted through the F-test and t-test. Descriptive analysis results showed that the employce performance variable was classified as good, the training effectiveness variable was classified as good, and the work discipline variable was also classified as good. The results of the t-test indicated that, partially, the training effectiveness variable had a positive and significant effect on employee performance. Similarly, the work discipline variable had a positive and significant effect on employee performance. The results of the F-test showed that, simultaneously, the training effectiveness and work discipline variables had a significant effect on employee performance. The determination analysis indicated that the two independent variables in this study explained 37.6% of the variation in employee performance at the Class B Search and Rescue Office, Maumere, Sikka Rege